Estudo retrospectivo de implantes osseointegrados instalados imediatamente após exodontias - Carrera, Emanuelle Teixeira [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
From early man tried to restore missing teeth using human teeth and animal bone carved pieces of ivory and pearls. Through the result of much research, materials, improvement of technique, and also the development of implants, currently, these are becoming one of the top choices for rehabilitation of patients suffering from partial or total edentulism. The installation of implants in the alveolus immediately after the extraction has been reported by many authors, aiming to reduce time and cost of treatment to eliminate the waiting period for healing to occur of the socket, reducing the number of operations preserve height, alveolar bone thickness and size of the soft tissue to promote osseointegration. The objective of this work was through a retrospective study evaluating the success of integrated implants installed immediately after tooth extraction, considering the area, type of prosthesis and whether with or without biomaterials. We analyzed 500 clinical records, and these were used only in that case conducted by extractions and immediate installation of implants and these are presented as a function over a period of one to five years. Among the 500 records analyzed, only 100 records (20%) were from patients who underwent surgery implant installed immediately after extraction.Of the 197 implants placed, 86 implants in the maxilla and 111 mandible and got up to 97.46% of successful cases. As for the types of prostheses on implants, used protocol, overdenture and fixed (total, partial and individual). Of the 100 records, it was observed that in 33% of cases there was a need for the use of grafts and / or biomaterials. It can be concluded that immediate implants are indicated when well yes, an excellent choice. The anterior mandible and prosthesis type overdenture protocol and have high success rates. The need for the use of bone graft / bimaterial not affect the results

Desde muito cedo o homem tentou repor os dentes perdidos usando dentes humanos e de animais, osso esculpido, pedaços de marfim e pérolas. Por meio do resultado das muitas pesquisas, materiais, aprimoramento da técnica, e também o desenvolvimento de implantes, atualmente, estes estão se tornando uma das principais opções para a reabilitação dos pacientes que sofrem do edentulismo parcial ou total. A instalação de implantes no alvéolo imediatamente após a exodontia tem sido relatada por vários autores, com o intuito de diminuir o tempo e custo do tratamento, eliminar o período de espera para que ocorra a cicatrização do alvéolo, reduzir o número de cirurgias, preservar altura, espessura óssea alveolar e dimensão do tecido mole, a fim de promover a osseointegração. O objetivo deste trabalho foi por meio de um estudo retrospectivo, avaliar o sucesso de implantes osseointegrados, instalados imediatamente após as exodontias, considerando a região, tipo de prótese e se está associado ou não à biomateriais. Foram analisados 500 prontuários clínicos de pacientes tratados com implantes osseointegrados, sendo que destes foram utilizados somente aqueles em que os casos conduzidos por meio de exodontias e instalação imediata de implantes e estes se apresentavam em função num período de um a cinco anos. Dentre os 500 prontuários analisados, apenas 100 prontuários (20%) eram de pacientes que foram submetidos a cirurgia de implante instalados imediatamente após a extração. Dos 197 implantes instalados imediatamente, 86 implantes foram instalados na maxila e 111 na mandíbula e obtive-se 97,46% de sucessos para os casos. Quanto aos tipos de prótese sobre os implantes, utilizaram protocolo, overdenture e fixa (total, parcial e individual). Dos 100 prontuários, observou-se que em 33% dos casos houve a necessidade do uso de enxertos e/ou biomateriais. Pode-se...
Keywords: Implantes dentários; Osseointegração; Extração dentária; Dental implants